The Madness of Imagining New Worlds - Ariza, Mercedes; Giovanna Biscu, Maria; Isabel Fernándes García, María (SCENARIO: Journal for Performative Teaching, Learning, Research, 2007)
This paper presents some reflections that emerged from a research project developed in the Department of Interdisciplinary Studies in Translation, Languages and Cultures (SITLeC) of the University of Bologna. This three-stage project was based on language mediator training and the teaching/acquisition of intercultural communicative competence through theatre. During an eight-month workshop, a group of Italian students – beginners in Spanish – engaged in a series of extracurricular activities, resulting in the public performance of a play written in verse by Lope de Vega. Under the researchers’ supervision, students analysed the play from a linguistic and (inter)cultural perspective, giving special emphasis to the discovery of the other, the encounter of the Old and the New World and the miscommunication caused by lack of understanding in intercultural situations. All these aspects helped students to explore a wide range of verbal and nonverbal communicative strategies, as well as to increase their foreign language proficiency and develop empathy. The in-depth analysis of the play and of the emblematic character of Columbus, whose imagination is capable of inventing new worlds even before discovering them, showed students that the real shipwreck in intercultural encounters is incommunicability itself and that, in order to communicate, one needs to be an ‘apostate translator’. This paper presents some reflections that emerged from a research project developed in the Department of Interdisciplinary Studies in Translation, Languages and Cultures (SITLeC) of the University of Bologna. This three-stage project was based on language mediator training and the teaching/acquisition of intercultural communicative competence through theatre. During an eight-month workshop, a group of Italian students – beginners in Spanish – engaged in a series of extracurricular activities, resulting in the public performance of a play written in verse by Lope de Vega. Under the researchers’ supervision, students analysed the play from a linguistic and (inter)cultural perspective, giving special emphasis to the discovery of the other, the encounter of the Old and the New World and the miscommunication caused by lack of understanding in intercultural situations. All these aspects helped students to explore a wide range of verbal and nonverbal communicative strategies, as well as to increase their foreign language proficiency and develop empathy. The in-depth analysis of the play and of the emblematic character of Columbus, whose imagination is capable of inventing new worlds even before discovering them, showed students that the real shipwreck in intercultural encounters is incommunicability itself and that, in order to communicate, one needs to be an ‘apostate translator’.